Empowering Local Wisdom-Based Food Micro, Small, and Medium Enterprises (MSMEs) to Enhance Business Competitiveness in Ladang Bambu Village, Medan Tuntungan District, Indonesia - A M Hatuaon Sihite; Ikwan Lubis; Nurin Natiqoh Lubis; Maringan Sianturi (Journal of Economics, Management and Accounting (JEMA), 2026)
Local wisdom-based Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in promoting local economic growth while preserving cultural heritage. This study aims to analyze the current condition of local food-based MSMEs, identify the challenges faced by business actors, and formulate empowerment strategies to improve their competitiveness in Ladang Bambu Village, Medan Tuntungan District. This research employed a qualitative approach using a case study method. Data were collected through observations, in-depth interviews, and documentation involving MSME owners, village officials, and related stakeholders. Data were analyzed descriptively through data reduction, data presentation, and conclusion drawing. The findings indicate that local wisdom-based food MSMEs possess significant development potential through the utilization of local raw materials and the preservation of traditional culinary products. However, several obstacles remain, including limited managerial capabilities, low product innovation, inadequate digital marketing skills, and restricted access to business financing. Recommended empowerment strategies include entrepreneurship training, business management mentoring, product and packaging innovation, utilization of digital technology for marketing, and strengthening collaboration among local governments, higher education institutions, and MSME actors. The implementation of these strategies is expected to enhance MSME competitiveness, expand market access, increase community income, and preserve local wisdom as a valuable cultural identity.